“Balkans” in Russian Encyclopedic Dictionaries of First Half of 19th Century - K. A. Kasatkin (Научный диалог)
The ways of representing the Balkan Peninsula that existed in Russia in the first half of the 19th century are analyzed in the article. The sources for the study were encyclopedic dictionaries of the first half of the 19th century. (A.A. Plyushar, L.I. Zeddeler, A.V. Starchevsky), as well as an unpublished work by I.P. Liprandi “The Experience of the Word Interpreter of the Ottoman Empire”. The author argues that for a long time the Balkan Peninsula was not perceived as a single region with a set of historically deter-mined features. Arguments are presented confirming that certain areas of the peninsula were elements of different discourses. The relationship between the choice of a particular register of descriptions by the authors of the dictionaries and the political affiliation of the described regions of the Balkan Peninsula is shown. The relationship between the choice of a particular register of descriptions by the authors of the dictionaries and the political affiliation of the described regions of the Balkan Peninsula is shown. A special attitude of the authors of encyclopedias to Serbia and Greece, the newly formed states on the territory of the Balkan Peninsula, has been established. Examples are given that show the duality of their images in the Russian narrative in the first half of the 19th century.